Effects of Anionic and Nonionic Surfactants on Wettability, Gas Sorption and Water Retention in Shale - ABDULELAH, HESHAM ESMAIL SAIF (2018)
The implication of wettability alteration by surfactants in gas sorption and fracturing fluid retention have never been experimentally in shale. In this study, the influence of the wettability change by anionic and nonionic surfactants on gas sorption and water retention in shale was systematically investigated.